2006
DOI: 10.1111/j.1743-6109.2005.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Dyspareunia and Urinary Sensory Symptoms in India: Population-Based Study

Abstract: Introduction Population level estimates of sexual dysfunction in less developed settings where sexuality is not openly discussed or is culturally constrained are lacking. Aim To determine the prevalence of dyspareunia and identify associated symptoms and sociocultural factors. Methods Data from a population-based national level family health sample survey con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The substantial co-existence of urinary sensory symptoms and dyspareunia identified in the present study would be compatible with the hypothesis that, in a proportion of women experiencing dyspareunia, there is an underlying visceral hyperalgesia that has arisen spontaneously or following a sensitizing episode such as urinary tract or sexually transmitted infection ). An association between urinary sensory symptoms and dyspareunia was reported by Laumann et al (1999) and similar findings were identified in analysis of Indian population data (Padmadas et al, 2006). However, we also showed some common but some differential patterns of statistical associations when the additional symptom of urinary incontinence was considered.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The substantial co-existence of urinary sensory symptoms and dyspareunia identified in the present study would be compatible with the hypothesis that, in a proportion of women experiencing dyspareunia, there is an underlying visceral hyperalgesia that has arisen spontaneously or following a sensitizing episode such as urinary tract or sexually transmitted infection ). An association between urinary sensory symptoms and dyspareunia was reported by Laumann et al (1999) and similar findings were identified in analysis of Indian population data (Padmadas et al, 2006). However, we also showed some common but some differential patterns of statistical associations when the additional symptom of urinary incontinence was considered.…”
Section: Discussionsupporting
confidence: 83%
“…Pain was more common among younger and less educated women. Another population based study in India based on the National Family Health Survey reported a prevalence of 12.6%, which was particularly high among newly married young women (Padmadas, Stones, & Matthews, 2006). Data from North America and Europe highlight the associations among urinary incontinence, urinary sensory complaints, pelvic floor disorders, and dyspareunia (Barber, Visco, Wyman, Fantl, & Bump, 2002;Gordon et al, 1999;Handa, Harvey, Cundiff, Siddique, & Kjerulff, 2004;Shaw, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Sexual pain, which was reported by 7.1% females, is relatively lower to the reported findings of 12.6–25.5% [8,17,26–28]. In a study on Indian women, 12.6% reported dyspareunia with a higher prevalence among newly married and younger women, among Muslims, rural residents, and among traditional contraceptive method users or nonusers [38]. Among men, sexual pain was reported in 3%, which is comparable to 2.4% reported from another epidemiological study [28].…”
Section: Discussionmentioning
confidence: 99%
“…[3], and Ackerman [2]), but it was the least frequently observed disorder in anxious patients. In a population‐based study in India, dyspareunia with overall prevalence of 12.5% was significantly more common among individuals who had urinary sensory symptoms when compared with their counterparts [20].…”
Section: Discussionmentioning
confidence: 99%